Evaluation of the Role of Losartan in the Prevention of Benign Prostate Hyperplasia in Rats - Shahid, Arooj; Waheed, Akbar; Ali, Shabana; Farhat, Kulsoom; Mehmood, Sikandar; Amin, Mehwish (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the preventive role of Losartan in testosterone-induced Benign Prostate Hyperplasia in an adult rat model. Study Design: Laboratory-based experimental study. Place and Duration of Study: National Institute for Health, Islamabad Pakistan, for four weeks in Oct 2021. Methodology: A total of ninety (n=90) rats were divided into three equal Groups, having thirty rats each. In group-A, no active intervention was carried out. In groups B and C, subcutaneous injections of testosterone were administered daily for 28 days to induce a Benign Prostate Hyperplasia model. In group-C, Losartan was administered daily. Animals were sacrificed after the study period of 4 weeks. The animal and prostatic weights were measured to calculate the prostatic index. Blood samples were taken to assess Prostate-Specific Antigen levels, and prostate samples were preserved for histo-pathological analysis. Results: Mean prostatic weight, prostatic index and serum Prostate-Specific Antigen showed a statistically significant decrease in group-C, where Losartan was given, compared to the disease control group-B (p-value <0.001). Moreover, histo-pathological features like glandular and stromal hyperplasia and the formation of intra-luminal papillary folds were significantly reduced in the drug-treated group-C compared to group-B. Conclusion: Losartan is an effective drug for the prevention of Benign Prostate Hyperplasia.